Removal of Congo Red From Aqueous Solutions at Hardened Cement Paste Surfaces - Wagner, Matthias; Eicheler, Christina; Helmreich, Brigitte; Hilbig, Harald; Heinz, Detlef (Frontiers in Materials, 2020)
The removal of azo dyes is a critical issue in current textile industry wastewater treatment. In contemporary wastewater management, many structures that are in direct contact with wastewater are constructed with concrete. In this contribution, the removal of Congo red from aqueous solutions by the material in the surface of hardened binder paste was studied in multiple exposure experiments. Flat prisms made with ordinary Portland cement (OPC) and ground granulated blast-furnace slag (GGBS) were stored in different aqueous solutions. The powdered surface material of these flat prisms was used as a substrate for the removal of Congo red from aqueous solutions. Storage in sodium sulfate solution lead to the formation of hydrotalcite nanosheets on the surfaces of hardened binder pastes rich in magnesium provided by the GGBS. These nanosheets resulted in a large specific surface area and increased the discoloration capacity with respect to binder mass. The results also suggest that the carbonation of ettringite and C-S-H can provide fresh calcite that can act as a secondary adsorbent. The results of this study suggest that cementitious binders with high magnesium contents could contribute to the removal of azo dyes from industrial wastewater by providing economically attractive treatment materials.